Immunosuppressive Microenvironment Revealed by Immune Cell Landscape in Pre-metastatic Liver of Colorectal Cancer - Zeng, Dongqiang; Wang, Miaohong; Wu, Jiani; Lin, Siheng; Ye, Zilan; Zhou, Rui; Wang, Gaofeng; Wu, Jianhua; Sun, Huiying; Bin, Jianping; Liao, Yulin; Li, Nailin; et al. (Frontiers in Oncology, 2021)
Background: Colorectal cancer, the fourth leading cause of cancer mortality, is prone to metastasis, especially to the liver. The pre-metastatic microenvironment comprising various resident stromal cells and immune cells is essential for metastasis. However, how the dynamic evolution of immune components facilitates pre-metastatic niche formation remains unclear. Methods: Utilizing RNA-seq data from our orthotopic CRC mouse model, we applied single-sample gene set enrichment analysis and Cell type Identification By Estimating Relative Subsets Of RNA Transcripts to investigate the tumor microenvironment landscape of pre-metastatic liver, and define the exact role of MDSCs acting in the regulation of infiltrating immune cells and gene pathways activation. Flow cytometry analysis was conducted to quantify the MDSCs levels in human and mice samples. Results: In the current work, based on the high-throughput transcriptome data, we depicted the immune cell infiltration pattern of the pre-metastatic liver and highlighted MDSCs as the dominant altered cell type. Notably, flow cytometry analysis showed that high frequencies of myeloid-derived suppressor cells (MDSCs), was detected in the pre-metastatic liver of orthotopic CRC tumor-bearing mice, and in the peripheral blood of patients with stage I-III colorectal cancer (CRC). MDSCs accumulation in the liver drove immunosuppressive factors secretion and immune checkpoint score upregulation, consequently shaping the pre-metastatic niche with sustained immune suppression. Metabolic reprogramming such as upregulated glycolysis/gluconeogenesis and HIF-1 signaling pathways in the primary tumor was also demonstrated in the pre-metastatic liver with MDSCs infiltration. Some chemokines were identified as a potential mechanism for MDSCs recruitment. Conclusion: Collectively, our study elucidates the kinetics of MDSCs evolution during pre-metastatic niche transformation, and illuminates the latent biological mechanism by which primary tumors impact MDSC aggregation in the targeted liver.